Elucidation of catalytic NOx reduction mechanism in an electric field at low temperatures. Issue 14 (10th March 2022) - Shigemoto, Ayaka; Higo, Takuma; Narita, Yuki; Yamazoe, Seiji; Uenishi, Toru; Sekine, Yasushi
Abstract : We found that Pd-supported catalysts exhibit high TWC activity when a DC electric field is applied, even at temperatures lower than 473 K, and the reaction mechanism has been investigated. Abstract : As automobiles increasingly become electrically driven and as more engines and motors are used together, the exhaust temperatures of internal combustion engines are decreasing. Further improvement of exhaust gas purification catalyst performance is necessary. To purify nitrogen oxides, unburned hydrocarbons, and carbon monoxide simultaneously at low temperatures, electrothermal heating and plasma catalysis have been proposed, but these methods require high power consumption. Results of this study indicate that a direct current electric field applied to a Pd-supported catalyst shows high purification rates even at temperatures lower than 473 K under TWC conditions (NO–CO–C3 H6 –O2 –H2 O). For clarifying the reaction mechanism in this process, the adsorption of reactants was evaluated using in situ DRIFTS measurements in an electric field. Factors that improve the activity at low temperatures in the electric field were clarified.